Jernang (Daemonorops spp.) commercialization and its role for rural incomes and livelihoods in Southern Sumatra, Indonesia. Issue 3 (3rd July 2019) - Widianingsih, Nayu Nuringdati; Schmidt, Lars Holger; Theilade, Ida
ABSTRACT: Forest areas in Sumatra, Indonesia are continuously shrinking, leading to depletion of forest resources. Daemonorops spp ., locally known as Jernang, is one of the most sought-after non-timber forest products (NTFPs) and has a high commercial value. Recently, conversion of its forest habitat and growing international market demand have placed Jernang in the vulnerable species category on the IUCN Red List. Official statistics on Jernang trade and consumption are scant as it is part of the informal rural economy and customs data are aggregated, without specifying volumes of Jernang exported from Indonesia. The aim of this study was to investigate the contribution of Jernang to rural incomes with a particular focus on the producers (collectors and cultivators) and entrepreneur groups at the village level. In the present case study, the absolute income of Jernang to annual household economies ranged from 386 US dollars per adult equivalent units (USD/aeu) for Jernang collectors through 1389 USD/aeu for Jernang cultivators, and up to 2106 USD/aeu for entrepreneurs. The relative income from Jernang trade was highest for the cultivator and entrepreneur groups (54% and 64%, respectively). Collector households were the poorest group, both in terms of land ownership and income. The high relative contribution of Jernang to the incomes of cultivator households may prevent conversion of rural agroforestry systems to monocropping. Jernang cultivation may compensate for declining wild resources.